Research methods in sign language studies : a practical guide - Orfanidou, Eleni; Woll, B. (Bencie); Morgan, Gary, 1968- (Hoboken : Wiley-Blackwell, 2015)
'Research Methods in Sign Language Studies is a landmark work on sign language research, which spans the fields of linguistics, experimental and developmental psychology, brain research, and language assessment. Examines a broad range of topics, including ethical and political issues, key methodologies, and the collection of linguistic, cognitive, neuroscientific, and neuropsychological data Provides tips and recommendations to improve research quality at all levels and encourages readers to approach the field from the perspective of diversity rather than disability Incorporates research on sign languages from Europe, Asia, North and South America, and Africa Brings together top researchers on the subject from around the world, including many who are themselves deaf'--
'Provides recommendations from the experts to improve research quality at all levels and encourages readers to approach the field from the perspective of diversity rather than disability'--
Acknowledgments8 Research Methods for Studying the Form of Signs; Research Question; Data and Data Collection; Signers; Equipment: Prompts and Cameras; Annotation: Transcription and Coding; Data Storage: Database and Spreadsheet Software; Analysis; Conclusion; Suggested Readings; References; Acknowledgments; 9 Methods of Research on Sign Language Grammars; Basic Vocabulary; Lexicon Studies; Verb Classification and Grammatical Roles; Sentence Types and Discourse Structure; Coding Strategies; Suggested Readings; References; 10 Documentary and Corpus Approaches to Sign Language Research.
Machine generated contents note: Notes on Contributors vii Introduction 1 Eleni Orfanidou, Bencie Woll, and Gary Morgan Part I Collecting Data WITH the Deaf Community 5 1 Ethics, Deaf-Friendly Research, and Good Practice When Studying Sign Languages 7 Jenny Singleton, Amber Martin, and Gary Morgan 2 The Deaf Community as a'Special Linguistic Demographic': Diversity Rather Than Disability as a Framework for Conducting Research with Individuals Who Are Deaf 21 Thomas E. Allen 3 Dissemination and Transfer of Knowledge to the Deaf Community 41 Robert Adam Part II Different Ways of Collecting Sign Language Data 53 4 Collecting and Analyzing Sign Language Data: Video Requirements and Use of Annotation Software 55 Pamela Perniss 5 Transcription and Notation Methods 74 Onno A. Crasborn 6 Instrumented Measures of Sign Production and Perception: Motion Capture, Movement Analysis, Eye-Tracking, and Reaction Times 89 Martha E. Tyrone Part III Collecting Linguistic Data on Sign Languages 105 7 Sign Language Fieldwork 107 Victoria Nyst 8 Research Methods for Studying the Form of Signs 123 Rachel Channon 9 Methods of Research on Sign Language Grammars 141 Carol A. Padden 10 Documentary and Corpus Approaches to Sign Language Research 156 Jordan Fenlon, Adam Schembri, Trevor Johnston, and Kearsy Cormier 11 Methods in Carrying out Language Typological Research 173 Nick Palfreyman, Keiko Sagara, and Ulrike Zeshan 12 Data Collection in Sociolinguistics 193 Joseph C. Hill Part IV Collecting Cognitive Data on Sign Languages 207 13 Research Methods in Psycholinguistic Investigations of Sign Language Processing 209 Jill P. Morford, Brenda Nicodemus, and Erin Wilkinson 14 Methods in Bimodal Bilingualism Research: Experimental Studies 250 Ronice Muller de Quadros, Deborah Chen Pichler, Diane Lillo-Martin, Carina Rebello Cruz, L. Viola Kozak, Jeffrey Levi Palmer, Aline Lemos Pizzio, and Wanette Reynolds 15 Studying Sign Language Acquisition 281 Amy M. Lieberman and Rachel I. Mayberry 16 Research Methods in Studying Reading and Literacy Development in Deaf Children Who Sign 300 Fiona E. Kyle Part V Collecting Brain Data on Sign Languages 319 17 Studying Sign Language Processing Using Functional Neuroimaging Techniques: FMRI, ERP, MEG and TMS 321 Cheryl M. Capek and Helen J. Neville 18 Studying Sign Language Disorders: Considering Neuropsychological Data 336 Peter C. Hauser, David Quinto-Pozos, and Jenny L. Singleton 19 Using and Developing Language and Cognitive Assessments with Deaf Signers 352 Tanya Denmark and Joanna Atkinson Index 000.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Sign language -- Study and teaching; Sign language -- Research; Linguistics; Sign language -- Research; Sign language -- Study and teaching; Electronic books; Electronic books